An Analysis of the Diversity and Inclusion Content Featured on Ophthalmology Residency Program Web Sites - Samuel A. Cohen; Landon E. Cohen; Suzann Pershing (Journal of Academic Ophthalmology, 2022)
Introduction Ophthalmology departments have been stated to be among the least diverse clinical departments at United States medical schools. Improvement requires recruiting a pipeline of diverse trainees. Residency program Web sites represent a potential diversity and inclusion recruitment tool. This study assesses how ophthalmology residency program Web sites demonstrate a commitment to diversity and inclusion. Methods We analyzed the diversity and inclusion content of 116 ophthalmology residency program Web sites in April 2021. Main outcome measures were the presence of 12 diversity and inclusion elements on program Web sites, based on prior work and Accreditation Council for Graduate Medical Education guidelines: nondiscrimination statement, diversity and inclusion message, community resources, extended faculty or resident biographies (including hobbies, etc.), faculty photos, resident photos, additional financial resources for trainees, wellness resources, mental health resources, health disparities/community engagement, and diversity council. We used Mann–Whitney U and Kruskal–Wallis tests to assess whether residency program characteristics such as rank, size, university affiliation, and geographic location were associated with commitment to diversity and inclusion on affiliated residency Web sites. Results Ophthalmology residency program Web sites included a mean of 4.4 ± 2.1 diversity elements. Sixteen percent of programs featured more than half (7 + ) of the evaluated diversity elements. The most featured common diversity elements included resident photos (85.3%), faculty photos (78.4%), and community resources (64.3%). Extended faculty biographies (2.6%), mental health resources (9.5%), and diversity council information (11.2%) were less commonly showcased. Top-ranked programs (7.6 ± 1.8, p < 0.0001) and university-based/-affiliated programs (4.7 ± 2.8, p = 0.0039) displayed more diversity elements than lower-ranked (4.1 ± 1.8) and community-based programs (2.8 ± 1.7). Conclusion Most ophthalmology residency program Web sites feature less than half of the 12 diversity and inclusion elements included in this study, suggesting room for improvement. By drawing attention to program diversity and inclusion efforts, Web sites offer a potential tool for residency programs to consider in their recruitment efforts for diverse trainees. Incorporating the diversity and inclusion elements analyzed in this study represents a low-burden way to signal a greater commitment to diversity that could help programs recruit diverse applicants.